DNA-Binding Properties of YbaB, a Putative Nucleoid-Associated Protein From Caulobacter crescentus - Pal, Parul; Modi, Malvika; Ravichandran, Shashank; Yennamalli, Ragothaman M.; Priyadarshini, Richa (Frontiers in Microbiology, 2021)
Nucleoid Associated Proteins (NAPs) or Histone-Like Proteins (HLPs) are DNA binding proteins present in bacteria that play an important role in nucleoid architecture and gene regulation. NAPs affect bacterial nucleoid organization via DNA bending, bridging or forming aggregates. EbfC is a nucleoid associated protein identified first in Borrelia burgdorferi, belonging to YbaB/EbfC family of NAPs capable of binding and altering DNA conformation. YbaB, an orthologue of EbfC found in E. coli and H. influenzae, also acts as a transcriptional regulator. YbaB has a novel tweezer-like structure and binds DNA as homodimers. The homologues of YbaB are found in almost all eubacterial species, suggesting a conserved function, yet physiological role in many bacteria is not well understood. In this study, we characterized the YbaB/EbfC family DNA binding protein in Caulobacter crescentus. C. crescentus has one YbaB/EbfC family gene annotated in the genome (YbaBCc) and it shares 41% sequence identity with YbaB/EbfC family NAPs. Computational modelling revealed tweezer-like structure of YbaBCc, characteristic of YbaB/EbfC family of NAPs. N-terminal–CFP tagged YbaBCc localized with the nucleoid and is able to compact DNA. Unlike B. burgdorferi EbfC protein, YbaBCc protein is a non-specific DNA-binding protein in C. crescentus. Moreover, YbaBCc shields DNA against enzymatic degradation. Collectively, our findings reveal that YbaBCc is a small histone-like protein and may play a role in bacterial chromosome structuring and gene regulation in C. crescentus.